PENERAPAN MODEL PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS III SD NEGERI KUALA TRANG - Fetro Dola Syamsu; Siti Sahara; Febry Fahreza (Jurnal Genta Mulia, 2025)
This study aims to determine the application of differentiated learning models in science learning and to determine student learning outcomes through the application of differentiated learning models in science learning of grade III of Kuala Trang State Elementary School. The type of research used is classroom action research. The instruments used to collect data in this study consisted of observation sheets, test sheets, and validation sheets. The results of this study can be concluded that the application of differentiated learning models in this study contains four main stages of activities, namely planning, action, observation, and reflection and is carried out in the form of 2 repeated cycles. The application of differentiated learning models is very effective in improving student learning outcomes in the material on the motion of objects. This is evidenced by the increasing percentage of student learning outcomes in each cycle. By using several cycle stages, namely pre-cycle, cycle I, and cycle II. In the pre-cycle of 16 students, there were 3 students who completed or (18.75%) and 13 students did not complete (81.25%), while in cycle I of 16 students, there were 8 students who completed or (50.00%) and 8 students who did not complete (50.00%). Furthermore, in cycle II, there was a very significant increase in student learning outcomes, namely from 16 students, there were 14 students who completed or (87.5%) and only 2 students who did not complete (12.5%).